The Effect of Earnings Yield on Assessments of the Association Between Annual Accounting Income Numbers and Security Prices. - Basu, S. (The Accounting Review, 1978)
Abstract ABSTRACT: The role of accounting data in the formation of security prices in general, and the process by which such prices adjust to the announcement of external accounting numbers in particular, has attracted considerable attention. Extending the research conducted by Ball and Brown, this paper examines the degree to which earnings yields of corporate equities affect the association between annual income numbers and security prices. The propositions of two alternative views on this association are analyzed in the context of a normative model of investor expectations and security price behavior. The empirical evidence reported in this paper leads to the conclusion that, by and large, the level of association between annual income numbers and security prices is not independent of the earnings yields of common stocks. This finding indicates that either there exists frictions in the security price adjustment process or the extant two-parameter model of market equilibrium is mis-specified. Finally, some important implications of these results for capital market researchers, as well as for investors are provided.